Causes of deforestation in the Brazilian Amazon: a qualitative comparative analysis - Scouvart, M.; Adams, R.T.; Caldas, M.; Dale, V.; Mertens, B.; Nédélec, V.; Pacheco, P.; Rihoux, B.; Lambin, E.F. (2007)
The authors used a configurational comparative approach, the Qualitative Comparative Analysis (QCA), to study multiple causal interactions characterizing deforestation in the Brazilian Amazon. Their data set is based on seven local case studies at three time periods. Results reveal a limited number of pathways describing the articulation of causes of deforestation in the Brazilian Amazon under different contexts. Roads are often combined with biophysical conditions and the occurrence of extractive activities in the explanation of deforestation. This study reached conclusions via a reproducible and formal procedure that was applied at a regional scale while accounting for the geographic diversity of land-use trajectories.